Prospects and challenges for use of CAR T cell therapies in solid tumors. (3rd May 2020) - Ramakrishna, Sneha; Barsan, Valentin; Mackall, Crystal
ABSTRACT: Introduction : Chimeric antigen receptor (CAR) T cell therapy has provided patients with relapsed/refractory B cell malignancies a new therapeutic option, but this class of therapeutics has not demonstrated consistent therapeutic benefit in solid tumors. Areas Covered : Here we review the literature to identify numerous factors that contribute to this discrepancy, using pediatric cancers as a platform to understand these limitations. We discuss an inability to target highly and homogenously expressed lineage-associated antigens due to risks of on-target off-tumor toxicity, T cell dysfunction related to T cell exhaustion and the suppressive tumor microenvironment (TME), and inefficient CAR T cell trafficking into solid tumors. As our understanding of the biology of CAR T cells improves and innovations in engineering CAR platforms emerge, next generation CAR T cell therapeutics designed to overcome these challenges will enter the clinic for testing. Expert Opinion : New approaches to address the challenges that have limited the efficacy of CAR T cell therapeutics in solid tumors are emerging. These approaches include next-generation CAR T cell engineering to overcome antigen heterogeneity, to mitigate T cell exhaustion and to prevent suppression by the TME, as well as novel approaches for regional delivery to facilitate tumor T cell trafficking.